Internalisasi Nilai-Nilai Moderasi Beragama di Kalangan Pasangan Nikah Beda Agama Masyarakat Tosari-Pasuruan - Rudi Adi (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2025)
This study aims to examine the internalization of religious moderation values ​​among interfaith married couples in Tosari, Pasuruan. This is motivated by the fact of religious plurality that occurs in the intended location. The important question to be answered is how interfaith married couples in Tosari, Pasuruan internalize the values ​​of religious moderation in their family life. Methodologically, this study is based on a field study based on emic data tracking. Through this method, the study found that the internalization of religious moderation values ​​in the families of interfaith married couples in Tosari, Pasuruan, occurs through four main pillars: tolerance, commitment to nationality, anti-violence, and accommodation to local traditions. This is of course not only related to efforts to maintain household harmony but also to strengthen social cohesion in a multicultural society.